Action Research for Building Marketing Capacity to Empower Burley Tobacco Farmers in Thailand to Transition From Tobacco Cultivation to Alternative Crops or Livelihoods - Phetphum, Chakkraphan; Wangwonsin, Artittaya; Keeratisiroj, Orawan; Boonyom, Supanee (Nicotine & tobacco research, 2025)
Burley tobacco farmers in Thailand face a declining quality of life, pushing them to seek alternative income sources. This action research investigated the effectiveness of the marketing capacity-building training in empowering these farmers to transition toward alternative crops. This action research employed the Kemmis and McTaggart model and was conducted over 7 months (April-October 2023) in Thap Phueng Subdistrict, Sukhothai. Forty-two Burley tobacco farmers participated in planning, implementing, and evaluating a marketing capacity-building intervention through five structured workshops. These covered business model design, online product sales, product photography and video creation, packaging and delivery, and advertising and promotion. Quantitative data were collected via self-administered questionnaires to assess intention to quit tobacco cultivation and self-efficacy in marketing capacity, using a 0-10 numeric rating scale. Paired t-tests were used to compare pre- and post-intervention scores. Qualitative data were obtained from two focus group discussions with 12 purposively selected participants. Focus group sessions were conducted using a semi-structured interview protocol and facilitated by experienced qualitative researchers. Each session was audio-recorded with consent, transcribed verbatim, and analyzed using thematic analysis to identify perceived enablers and barriers related to marketing capacity development. The intervention led to a statistically significant increase (p < .001) in participants' perceived self-efficacy for marketing capacity, rising from a mean score of 27.19-59.59. However, the intention to quit tobacco cultivation showed no statistically significant change (p = .243). Qualitative findings from focus group discussions revealed that farmers attributed the success of the intervention to hands-on training, peer engagement, and needs-based activities. Key challenges included limited digital literacy and poor access to technology-particularly among older participants. This study highlights the potential of marketing capacity development in enhancing farmers' self-efficacy, which may support a gradual transition from tobacco cultivation. However, challenges such as limited education and digital literacy-especially among older farmers-remain. Participant feedback points to the need for financial incentives and digital support. Collaborative policy efforts are essential to enable sustainable alternatives. This study highlights the role of marketing capacity-building in enhancing farmers' self-efficacy-a key enabling factor for transitioning from tobacco cultivation. While the intention to quit tobacco farming did not significantly change during the study period, participants reported increased confidence in marketing skills and identified key supports needed to make a successful shift. These included financial incentives, guaranteed market access, and digital literacy support, particularly for older farmers. Policymakers and stakeholders are encouraged to collaborate in designing inclusive support programs that address these needs. Future research should assess long-term outcomes and evaluate scalable models of intervention.